Organisational Control System in a Continuous Improvement Environment: Special Reference to the Role of Management Accounting - Pérez, Bernabé Escobar; González González, José María; Gallardo, Antonio Lobo (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2008)
In today's environment, one of the top priorities for organisations is to reduce costs without affecting dramatically organisation survival. The aim of this paper is to provide evidence on (1) the importance of Management Accounting information for continuous improvement processes and (2) the role of certain Control System elements for the implementation of this strategy. A longitudinal case study has been conducted for this purpose at the Spanish subsidiary of a multinational chemical group. This chemical processing company introduced a cost reduction project in the middle of 1990's. The most salient results were, on the one hand, the implementation of internal benchmarking practices based on information provided by Management Accounting, and, on the other hand, the important contribution of both formal and non-formal Control System elements to the successful achievement of the project's objectives.